Professional exposure to ionizing radiation and the occurrence of cataract - Đurović Branka; Đurović Branislav M.; Spasić-Jokić Vesna M. (Vojnosanitetski Pregled)
Radiation cataract is one of ensuing effects of ionizing radiation, since its threshold dose under which it does not occur, and above which it shows dose dependency, has been observed. Clinical course of radiation cataract is identical for all the types of ionizing radiation and is very typical. Minimal dose for progressive cataract formation is determined by the type of radiation, i.e., its relative biological efficacy, dose, and the duration of the exposure period. Theoretically, threshold dose existence does not exclude the incidence of cataract formation under significantly smaller doses, as well. The aim of this study was to analyze the incidence of cataract formation among the medical staff professionally exposed to ionizing radiation. Neither of the diagnosed cataracts had typical morphology, nor was the correlation established between the dose, exposure time, and the cataract formation. All the diagnosed cataracts were described as premature, and therefore ionizing radiation was considered as a co-factor in premature cataract formation in the examined groups.